Identity construction and negotiation of transgenders in interpersonal interaction a case study - Bumanglag, Krizia Rafaella S.; Glova, Nelfa M. (2019)
Social constructionism plays a major role on how people set their standards towards something especially identity. In the case of gender identities, people have acknowledged the presence of other identities apart from the binary male and female. The LGBTQ+++ community, even if they are being recognized, experiences different forms of harassment. This case study aims to find out how transgenders a) create their identities based from the layers proposed by Jung and Hecht?s Communication Identity Theory: personal, relational, enacted, and communal; and b) negotiate these identities in interpersonal interaction. There were six (6) cases elaborated in this study which yielded four (4) themes: transgenders construct their identity mainly rooting on how society dictates it to them, then, once they realize that they are neither of the binary male and female, they identify themselves based on how a transgender is being perceived. In negotiating these identities, they consider the different cases of discrimination that other transgender experience, and they get to be accepted based from their physical output-whether they are passable or not. There are three stages to transitioning to the transgender identity: mental, one?s sensibility and thought process is that of a woman; medical, the intervention of hormonal pills to reconfigure the body, and physical, the operational change of genitalia. While the study has been a milestone for transgender studies, there are still improvements that could be employed such as decoding the meaning of bayot, transgender, and passable for transgenders in the Philippines.
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2019